TRANSLATION ANALYSIS OF DIRECTIVE SPEECH ACTS IN "EAT PRAY LOVE" NOVEL AND ITS TRANSLATION INTO INDONESIAN - Fitriana, Irta (PRASASTI: Journal of Linguistics, 2013)
Translating utterances is not similar to translating sentences. It requires special attention as there is an intended meaning or message transferred by a speaker to a hearer. Context of the situation overshadowing the utterance must be obeyed carefully. Thus the messages will be easily revealed. Speech act is a way that allows the messages of utterances to be seen. Schiffrin (2001) stated that speech act is one of pragmatics’ basic ingredients arranging by words and corresponding to sentences and some ways to avoid kinds of misunderstanding in communication. The focus of speech act is illucution since it shows the intention of utterances uttered. It is also much correlated withtranslation. Intranslatingan utterance, itis not merelytranslated literally, butthere is also an intentionthat shouldbe translated. This paper is aimed to analyze directive speech act in Eat Pray Love and its translation into Indonesian. It tries to reveal the functions of directive speech acts, translation techniques used and the translation quality (readability, accuracy, and acceptability).Key words: speech act, directives, translation, readability, accuracy, and acceptability